The combination of atrial fibrillation and obstructive sleep apnea — is there a connection? - G. G. Arutyunyan; M. V. Agaltsov; K. V. Davtyan; O. M. Drapkina (Российский кардиологический журнал, 2018)
The review discusses the issue of the mutual influence of combination of atrial fibrillation (AF) and obstructive sleep apnea (OSA). In individuals with a combination of these pathologies, OSA can influence the easier realization of AF. The presence of respiratory disturbances in sleep reduces the effectiveness of all types of AF treatment (antiarrhythmic, surgical, electrical cardioversion). It is shown, that the treatment of OSA by the method of non-invasive ventilation support (CPAP-therapy) improves the results of catheter treatment of AF in the early postoperative period.